DEVELOPMENT OF SYMMETRIC MODEL FOR FLUID-STRUCTURE INTERACTION SIMULATION ON STEAM TURBINE ROTOR - Fauzi, Katanda Fajar; Choiron, Moch. Agus; Widodo, Agung Sugeng; Solikhin, Atfalus Solikhin (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2025)
Development of technology allows stress analysis of steam turbine rotor to be performed non-experimentally using Fluid-Structure Interaction (FSI) simulation. FSI modeling requires high computational power and a long time to complete. In this study, a symmetric model is used to reduce the computational time. The part size of the symmetric model is investigated for its influence on the FSI simulation results. The full, 1/5, 1/30, and 1 blade models were investigated. Fluid domain is solved by Computational Fluid Dynamic (CFD) simulation. Afterwards, pressure and temperature distributions are mapped to the structural simulation to determine the structural response in terms of stresses. The pressure distribution, temperature distribution, and stress distribution of each model were compared. The contours of pressure distribution, temperature distribution, and stress distribution have the same trend for all models. The pressure and stress value on sharp shape of the blade tip is slight difference due to insufficient number of elements.